Genomic characterization of the NAC transcription factors, directed at understanding their functions involved in endocarp lignification of iron walnut (Juglans sigillata Dode) - Yu, Anmin; Zou, Hanyu; Li, Ping; Yao, Xiaowei; Zhou, Zekun; Gu, Xu; Sun, Rui; Liu, Aizhong (Frontiers in Genetics, 2023)
The NAC (NAM, ATAF1/2 and CUC2) transcription factors (TF), one of the largest plant-specific gene families, play important roles in the regulation of plant growth and development, stress response and disease resistance. In particular, several NAC TFs have been identified as master regulators of secondary cell wall (SCW) biosynthesis. Iron walnut (Juglans sigillata Dode), an economically important nut and oilseed tree, has been widely planted in the southwest China. The thick and high lignified shell derived endocarp tissues, however, brings troubles in processing processes of products in industry. It is indispensable to dissect the molecular mechanism of thick endocarp formation for further genetic improvement of iron walnut. In the present study, based on genome reference of iron walnut, 117 NAC genes, in total, were identified and characterized. We found that the amino acids encoded by these NAC genes varied from 103 to 1264 in length, and conserved motif numbers ranged from 2 to 10. The JsiNAC genes were unevenly distributed across the genome of 16 chromosomes, and 96 of these genes were identified as segmental duplication genes. Furthermore, 117 JsiNAC genes were divided into 14 subfamilies (A-N) according to the phylogenetic tree based on NAC family members of Arabidopsis thaliana and common walnut (J. regia). Furthermore, tissue-specific expression pattern analysis demonstrated that a majority of NAC genes were constitutively expressed in five different tissues (bud, root , fruit, endocarp, and stem xylem), a total of 19 genes were specifically expressed in endocarp, and most of them also showed high and specific expression levels in the middle and late stages during iron walnut endocarp development. Our result provides a new insight into the gene structure and function of JsiNACs in iron walnut, and identification of key candidate JsiNAC genes involved in endocarp development, which may provide mechanistic insight in shell thickness formation across nut species.